Migrations of individually identified humpback whales between the Antarctic Peninsula and South America - Stevick, Peter T.; Aguayo, Anelio; Allen, Judith; Avila , Isabel C.; Capella, Juan; Castro , Cristina; Chater, Kim; Rosa, Luciano Dalla; Engel, Marcia H.; Felix, Fernando; Florez-Gonzalez , Lilian; Freitas, Ana; et al. (J. Cetacean Res. Manage., 2023)
Considerable uncertainty exists regarding the migratory destinations of humpback whales (Megaptera novaeangliae) from the Antarctic Peninsula region and the breeding grounds off the coasts of South America. Evidence is presented on the migratory patterns of Antarctic humpback whales based upon movements of individuals identified by natural markings as part of a large-scale international collaboration. Recapture rates were compared between animals from the low latitude breeding and calving areas along the northeastern (n=288) and northwestern (n=325) margins of South America with those identified in the high-latitude feeding areas in the region of the Antarctic Peninsula (n=535). The number of individuals re-sighted in the Antarctic Peninsula differed dramatically between eastern and western South America (c2=40.98, p=1.5 3 10–10). No individuals from Brazil were re-sighted in either the Antarctic Peninsula or off western South America. In contrast, 43 individuals from western South America were identified off the Antarctic Peninsula. These findings suggest that the northwest coast of South America represents an important breeding ground destination for at least some of the humpback whales that feed near the Antarctic Peninsula, but provide no support for movement between the Antarctic Peninsula and the east coast of South America.